Гончарне мистецтво як сучасна інновація в індустрії гостинності - Боровик, Тетяна Миколаївна; Сильчук, Тетяна Анатоліївна (My University, 2023)
Досліджено перспективи розвитку гончарного мистецтва в Україні. В контексті сучасних тенденцій гостинності, важливим аспектом є створення унікального та незабутнього досвіду для гостей. Гончарне мистецтво, як мистецтво ручного виготовлення керамічних виробів, виявляється значущим інструментом для досягнення цієї мети. Показано вплив впровадження гончарного мистецтва на готельний бізнес, культурну спадщину та задоволення потреб гостей. Стаття обговорює теоретичні аспекти та практичні застосування гончарного мистецтва у сфері гостинності. Встановлено, що використання гончарного мистецтва, як елементу бренду готелю, позначить його унікальність та зверне увагу на культурні цінності країни. Підкреслено важливість розвитку гончарного мистецтва в готелях для збереження культурної спадщини та підвищення привабливості готельного сектору в Україні

In the modern world, the hospitality industry is constantly influenced by various trends and innovations. Among these innovations, pottery art is worth highlighting as an exceptionally interesting and unique aspect. This article explores the role of pottery art in the hospitality industry. The paper analyzes how pottery art can become a key factor in enhancing the attractiveness and competitiveness of hotels. Initiatives aimed at implementing pottery workshops in hotels are examined, where guests can not only observe artisans but also actively participate in creating their own ceramic masterpieces. The article also delves into the issues of interactivity and engaging guests in the process of crafting ceramic products through workshops and similar initiatives. The benefits of integrating pottery art into the hospitality industry are identified, including increased guest satisfaction, the creation of a unique hotel character, and drawing attention to national cultural values. The overarching conclusion is that pottery art represents an innovative approach that adds value to the hospitality industry, enhancing competitiveness and creating unforgettable experiences for guests
Keywords: гончарне мистецтво; готельний бізнес; туризм; культурна спадщина; національна ідентичність; кафедра готельно-ресторанної справи; pottery art; hotel business; tourism; cultural heritage; national identity